The Influence Of Education Finance Management On The Quality Of Education At Ibrahimy University, Situbondo District - Thayyib, Moh; Supardi, Supardi; Indah Handayani, Yuniorita (Relasi : Jurnal Ekonomi, 2024)
This study aims to analyze the influence of the educational financing and budgeting system, the implementation of educational financing, and the supervision of educational financingon the quality of education at Universitas Ibrahimy Situbondo. Research on the influence of educational financing management on the quality of education at Universitas Ibrahimywas an ex-post facto research.Itwas a type of research on data collected after an occurred facts or events. Typically, it belonged to a causal associative research design which was used to determine the influenceof educational financing management (educational budgeting system, implementation of educational financing, and supervision of educational financing) on the quality of education. The research method used in this research was quantitative with a survey method. The survey method was conducted in the form of a questionnaire which had distributed to the respondents in this study. The respondents were all officials, treasurers, and The Internal Finance Comptroller at Universitas Ibrahimy.Results indicated that simultaneously,independent variables (educational budgeting system, implementation of educational financing, and supervision of educational financing) had a fairly strong influence on the quality of education at Universitas Ibrahimy by 61.9%.